Strategi Kepala Madrasah dalam Rekrutmen Peserta Didik Baru di MA NU Asy ‘Ariyyah Tajungsari - Ambarwati, Ambarwati; Ngartianingsih, Ngartianingsih; Ni'am, Muhammad Khoirun (AL-BURHAN, 2024)
This research aims to describe the strategies and supporting and inhibiting factors implemented by the Madrasah Head in recruiting new students at MA NU Asy'ariyyah Tanjungsari Tlogowungu Pati. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with Madrasah Principals, recruitment staff, and parents of prospective students. Data analysis was carried out using data reduction, data presentation and drawing conclusions. Research results 1) the strategy consists of 3 steps, namely first, planning (planning) including meetings, determining targets and methods, second actuating (implementation) containing socialization, instruments, indicators of entry requirements for new students, provision of registration forms, and third evaluating (evaluation) contains method improvements and increases information on social media. 2) Supporting factors for collaboration between madrasa heads, teachers and TU staff and collaboration with related MTs institutions as well as inhibiting factors include lack of emerging ideas, lack of socialization personnel, and less than optimal use of social media.Keywords: headmaster, new students, recruitmen strategies